Methodology for Improving the Methodological System of Future Chemistry Teachers Through Mobile Software Applications - Dauekeeva Guljaxan Uralbaevna (Researchparks Publishing, 2026)
This study focuses on improving the methodological system of training future chemistry teachers through the use of mobile applications. In the context of digital transformation in education, the integration of mobile technologies into the teaching process has become increasingly important. The research examines the didactic potential of mobile applications, their interactivity, and their role in enhancing students’ independent learning skills. Particular attention is given to the use of mobile platforms in chemistry education, including simulation of chemical processes, visualization of complex concepts, and the development of personalized learning pathways. The study is based on competency-based approaches, principles of digital pedagogy, and innovative teaching strategies. The findings contribute to the development of practical recommendations for the effective use of mobile applications in the professional training of future chemistry teachers and improving the overall quality of education.